P294 Cushing syndrome and adrenal insufficiency induced by high dose prolonged intranasal betamethasone. (June 2019) - Reynolds, Claire; Agrawal, Pankaj; McCann, Aisling; O'Sullivan, Triona; Chroinin, Muireann Ni; O'Riordan, Stephen MP
Abstract : Iatrogenic Cushing syndrome and secondary adrenal insufficiency due to intranasal steroids is rare in children. A 7 year old boy was referred to the paediatric endocrine clinic with suspected Cushing syndrome. He presented with excessive weight gain, marked striae and hypertension. His GP had performed a morning cortisol <28nmol/L (171–800nmol/L). He had a background history of obstructive sleep apnoea for which he had been prescribed Betnesol 0.1% (Betamethasone sodium phosphate 1 mg/ml) nasal drops and Montelukast 4 mg daily. Physical examination revealed hypertrichosis on his back, buffalo-humped neck, and purple striae on his legs and inner thighs. He was Tanner stage 1, normal genitalia. Auxology: weight 46.1 kg (>99.6 th centile); height 124.6 cm (50 th -75 th centile), body mass index (BMI) 30 kg/m2 (>99.6 th centile) and blood pressure was 124/72 mmHg (>99 th centile).The drug history was reviewed in detail by our Paediatric Pharmacist and revealed that over the past 20 months, he had been using betamethasone nasal drops continuously, prescribed at a dose of 2 drops, twice daily, into each nostril. A total of 38 repeat prescriptions had been dispensed and he had been taking double the prescribed amount per month. The duration of use (20 months) also far exceeded the recommended indication (4–6weeks max). Laboratory investigations: blood glucose 4.7 mmol/L, early morning cortisol <28 mmol/L (171–800nmol/L) and ACTH <0.2 undetectable (1.1–13.2pmol/L). Renin and aldosterone, anti-21 hydroxylase antibodies, thyroid function tests, IGF-1, coeliac screen, and renal/liver/bone were all normal. A short synacthen test (250micrograms) confirmed HPA axis suppression for our patient (cortisol concentrations: <28nmol/L at time: 0 mins, 30 mins and 60 mins). This is gold standard diagnostic test when adrenal suppression is suspected. He was immediately commenced on replacement hydrocortisone therapy at a dose of 8–10 mg/m 2 /day. He was also educated on emergency hydrocortisone administration and stress dosing. He will continue on hydrocortisone until his HPA axis recovers. Betamethsone is a potent steroid 25–30 times more potent than hydrocortisone Conclusion: We describe a case of iatrogenic Cushing syndrome and adrenal insufficiency secondary to administration of long-term high-dose betamethasone nasal drops. Very few cases to date have been reported in the literature in children. Cushing syndrome caused by intranasal steroids is a rare event and more commonly occurs after oral or topical steroid use. Our patient was taking double the recommended dose for more than 20 months. Paediatricians must be aware of the complications of nasal steroid administration and long-term use should be avoided